An Analysis of English Language Teacher Training Needs: A Case Study in Primary Schools of East Lombok Regency - Rini Marliana; Azmussya'ni (Saniya Institute, 2023)
This study aims to analyze the training needs of English teachers in elementary schools in Lombok Timur Regency. The results showed that English teachers in elementary schools in Lombok Timur Regency have sufficient competence, especially in social and personality aspects, but still need significant improvement in professional aspects (language proficiency and material development) and pedagogical competence (implementation of innovative teaching methods). Teachers' training needs are very high, especially in material development, improving language proficiency (particularly speaking and listening), and developing teaching methodologies. Teachers have high motivation to participate in training, but feel that the training they have attended so far has been less relevant and less practical. Other findings also revealed that teachers experience limitations in language proficiency, teaching materials, teaching methods, and access to technology. Based on these findings, English teacher training programs in elementary schools in Lombok Timur Regency should be comprehensively designed, with a focus on improving language proficiency, developing teaching materials, adopting innovative teaching methodologies, and using technology. They should be practical, applicable, relevant, measurable, and sustainable. This study provides important implications for designing more effective training programs that meet the needs of elementary school English teachers.